Survey of Dental Anesthesiology program directors' preferences regarding the candidate application and interview process. Issue 9 (26th April 2021) - Whitmer, Thomas; Saraghi, Mana; Badner, Victor
Abstract: Purpose/Objectives: Dental Anesthesiology recently gained specialty recognition in 2019. Program directors' preferences for candidates applying to this newly recognized specialty are not well known. This study sought to assess these preferences by surveying the program directors of advanced dental education programs in Dental Anesthesiology. Methods and materials: The survey consisted of eleven questions on candidate qualities, academic application criteria, standardized examinations, shadowing, externships, sedation experience, and interview format. Results: The survey achieved a response rate of 100% with all nine program directors completing the survey. The study found that program directors tended to rank integrity, interpersonal/communication skills, assumes responsibility, team player, and reliability among the top five candidate qualities. Program directors tended to rank professional evaluations, institutional evaluations, externship, shadowing (a practicing anesthesiologist), and standardized tests among the top five academic application criteria. Program directors largely preferred differentiating candidates with a standardized examination, such as the Comprehensive Basic Science Examination (CBSE) or the creation of a new examination specific for Dental Anesthesiology application. Program directors largely recommended shadowing and externships but were largely indifferent to a candidate's experience or certification in sedation. All nine program directors opted for virtual interviews in 2020. Conclusions: The findings of this descriptive, cross‐sectional study may have significant implications for the candidate application and interview process into the field of Dental Anesthesiology.